LEGAL REGULATION OF TELEMEDICINE IN UZBEKISTAN (World Bulletin of Social Sciences, 2026)
This article examines current issues of the legal regulation of telemedicine in the Republic of Uzbekistan. The author analyzes the current state of the legislative framework, identifying key regulatory acts governing the digitalization of healthcare. Special attention is paid to systemic problems hindering the full implementation of telemedicine technologies: the absence of a specialized law, the uncertainty of the legal status of remote medical services, and issues of legal liability of doctors. Based on the analysis of national legislation and scientific opinions, specific ways to improve legal norms are proposed, including the need to adopt a law "On Telemedicine" and the standardization of protocols for the protection of patients' personal data.
Keywords: Telemedicine; digital healthcare; legal regulation